ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK REKLAME KOTA SURAKARTA - Guarddina Faahtika Subroto, Fadjar Harimurti & Suharno (Universitas Slamet Riyadi, 2017)
The purpose of this study to know the effect of total population, amount of industries and GDRP (Gross Domestic Regional Product) on advertising revenue tax. This study uses quantitative data. Data collection techniques by means of documentation and literature. Data analysis technique used is multiple regression, the classical assumption test, descriptive statistics, F test, t test, and test the coefficient of determination. The results of the analysis of determination coefficient of R2 = 0.980, meaning that the effect of variables total population, amount of industries and the Gross Domestic Regional Product of the advertising revenue tax is implanted at 98%. F test results indicate that there is a positive and significant effect of the total population, the amount of industries and the Gross Domestic Regional Product simultaneously on the advertising revenue tax. Total population has positive and significant effect on the advertisement revenue tax. Tha amount of industries has positive effect but no significant on advertisement revenue tax. Gross Domestic Regional Product has positive and significant effect on the advertisement revenue tax.Keywords: advertisement tax, advertisement revenue tax, total population, amount of industries